IC 9010 Mining Health And Safety In-House And Contract Research In Fiscal Year 1985 (The National Institute for Occupational Safety and Health (NIOSH), 1985)
This publication summarizes the research (in-house and contract projects) programmed by the Bureau of Mines for fiscal year 1985 (October 1, 1984-September 30, 1985) under its Health and Safety Technology Program. The objective of these projects is to provide an ordered and sequenced advance toward the Bureau's overall goal of providing the system technology required to create a more healthful and safer working environment for the Nation?s mining and minerals processing workers.